Environmental impact and nutrient adequacy of derived dietary patterns in Vietnam - Nguyen, Son D.; Biesbroek, Sander; Le, Tuyen D.; Feskens, Edith J. M.; Brouwer, Inge D.; Talsma, Elise F. (Frontiers in Nutrition, 2023)
Rationale and objective Improving diet quality while decreasing environmental impacts is an important challenge for a healthy and sustainable food system. Therefore, this study aims to analyse the most common dietary patterns per female household member and explore the diet quality and environmental impacts of these patterns. Methodology The nationally representative General Nutrition Survey of 2009-2010 (n=8225 households) was used to derive dietary patterns using principal component analysis (PCA) based on 18 food groups as input variables. Quintiles of the highest adherence (Q5) and lowest adherence (Q1) were generated based on the factor score of each dietary pattern. Nutrient adequacy and dietary diversity scores were calculated to measure diet quality, and greenhouse gas emission (GHGE) and blue water use (BWU) were selected as environmental impact indicators. Results Using PCA, three distinct dietary patterns were identified: an Omnivorous, Traditional, and Pescatarian pattern. Compared to the Traditional pattern, the Omnivorous and Pescatarian patterns (Q5s) were associated with a higher nutrient adequacy, with mean probability of adequacy of 0.51 in both patterns, compared to 0.45 in the Traditional pattern. However, environmental impacts in terms of GHGE and BWU per 2000kcal were considerably higher in the Omnivorous pattern (6.14 kg CO2-eq. and 0.15 m3/kg) compared to all other pattern’s Q5s. The GHGE was lowest in the Traditional pattern (4.18 kg CO2-eq.) and the Pescatarian pattern has the lowest BWU (0.12 m3/kg). Conclusion Despite that diet quality was slightly better in all three patterns compared to the average diet of the total population, environmental impact was also higher. Therefore, future research is needed to develop a more optimal diet that considers both diet quality and environmental impact to explore the trade-offs between diet quality and environmental impact.